Analisi Faktor Terhadap Penyimpangan Keuangan Negara Tahun 1999/2000 (Dengan Pendekatan Component Analysis) - Budi Manggala (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2000)
From the Audit Report for the fiscal year 1999/2000, it has been found some discrepancies in the government finance for as much as Rp 165.850 billion by The Supreme Audit Board (SAB). The SAB put these discrepancies in three categories, which are: (1) obedience to the rules; (2) economizing and efficiency on the government finance; and (3) effectiveness on achieving the goal. The purpose of this article is to have factor analysis by using the component model to determine the significance, correlation, and multicollinearities among these discrepancies on govenment finance.